Fake news: essência e aparência - Melati, Nathalia Martins (2022)
This thesis deals with the rhetorical production of fake discourse. We investigate the construction of the argumentation of fake news, or false information, as we prefer to name them. False information integrates the universe of informational disorder, or disinformation, as it is an effort to impose itself as part of public opinion, as doxa, that is, as a consolidated knowledge in the social bosom. The interest in false information was born from the effectiveness of these discourses. False information is persuasive, therefore rhetorical, because it changes the audience's mood about beliefs and events. Thus, we question how to apply the rhetorical theory to a discourse known to be false, since Rhetoric evades precisely who produces this type of discourse: the dishonest speaker. Our first hypothesis is that there is a connection between false information and kairos, the circumstances in which this discourse comes into being; and the second is that the functioning of social networks changes the argumentation of false information. Our aim is to establish categories of analysis for false information based on Rhetoric. To pursue this objective, we adopted a qualitative approach as a research method, divided into bibliographic survey, corpus selection, analysis and interpretation of results. Our corpus consists of eight publications in text or text and image on the side effects of vaccination against covid-19 posted on the social network Twitter. From the analysis, we realized how false information about the side effects of vaccines keeps up with its time. False information exists because it opposes doxa, hence the importance of the moment of publication for understanding the effect of this information on the audience. Our second hypothesis was also confirmed. For the audience of essence, that is, contrary to the speaker's advice of false information, the emotional appeal of the speech, the pathetic proofs, were the highlight; while for the audience the appearance, favorable to the speaker, the moral appeal of the speech, the ethical proofs, were more relevant. The identification between speaker and audience of appearance is crucial for the interaction of this audience with the discourse on social networks